Priorities in Strategic Personnel Management in Tourism and Hospitality - L. I. Donskova; M. G. Zavodchikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Topicality of problems of strategic HR management in complicated and uncertain current conditions is proved by importance of personnel in the field of tourism and hospitality and affected by professional qualities of employees, which stipulates the level of tourist satisfaction, efficiency and competitiveness of organization as a whole. The goal of the research is to identify priorities among alternative opportunities in strategic HR management in enterprises of tourist and hospitality industry. Methodology of the research is based on integration of systemic and strategic management. The model of strategic HR management and empiric data at enterprises of the hotel type show high personnel turnover, uneven employment, absence of social ways of stimulation, importance of economic ways of motivation usually available in large hotels. Therefore, each enterprise elaborates its own system of employee retaining on the basis of balancing material and non-material incentives and forms a complex approach to methods of HR management. Working-out of priorities in strategic HR management rests on provisions of strategy of organization development and its key components. As alternative opportunities the following trends were proposed: innovation HR management with IKT elements, research and analytical approach, Well-being concept.